Uji kelayakan validasi LKS beroerientasi HOTS dalam model inkuiri terbimbing pada materi kalor dan teori kinetik gas di kelas XI SMA/MA - Elsa Imelda; Yenni Darvina; Silvia Yulia Sari (PILLAR OF PHYSICS EDUCATION, 2019)
In the 21st century requires a variety of skills that must be mastered by someone, so that education is expected to be able to prepare successful human resources in life and quality in all endeavors to be able to compete against the millennium era. Skills in the 21st century that must be mastered include the four pillars of life, namely learning to know, learning to do, learning to be, and learning to live together, in learning activities including critical thinking skills, problem solving, collaboration, innovation, information literacy, and various other skills. To achieve these demands the government seeks to improve the quality of education by evaluating and developing the curriculum. Where the government developed curriculum at this time the revised 2013 curriculum in 2017. The reality in school shows that learning physics has not been done well, this can be seen from the lack of active students during the learning process and less improving students' higher order thinking skills. This research aims to determine the level of validity or behavior of the HOTS oriented worksheet in the guided inquiry model. This type of research is R&D (Research and Development) with the Borg and Gall development model. The data source in this study was obtained from the results of validation by 3 expert lecturers. Based on the results of the study, it was concluded that the HOTS-oriented worksheet in the guided inquiry model was appropriate for use in the physics learning process with a very valid category with an average of 82.26%.